Introduction to the Law of Property, Estate Planning and Insurance - Mayer, Don; Warner, Daniel; Siedel, George J.; Lieberman, Jethro K. (Open textbook library., 2012)
Introduction to the Law of Property, Estate Planning and Insurance is an up-to-date textbook that covers legal issues that students must understand relating to real estate (an especially important business asset), as well as estate planning and insurance. The text is organized to permit instructors to tailor the materials to their particular approach. The authors take special care to engage students by relating law to everyday events with their clear, concise and readable style. After introductory chapters covering the legal environment of business, Introduction to the Law of Property, Estate Planning and Insurance provides students with context and essential legal concepts relating to property rights and duties, estate planning, insurance, secured transactions, mortgages, and related topics. The text provides the vocabulary and legal savvy they will need when working with these concepts, which are critical to business planning and success.